9x+5=8x-6

Simple and best practice solution for 9x+5=8x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+5=8x-6 equation:


Simplifying
9x + 5 = 8x + -6

Reorder the terms:
5 + 9x = 8x + -6

Reorder the terms:
5 + 9x = -6 + 8x

Solving
5 + 9x = -6 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
5 + 9x + -8x = -6 + 8x + -8x

Combine like terms: 9x + -8x = 1x
5 + 1x = -6 + 8x + -8x

Combine like terms: 8x + -8x = 0
5 + 1x = -6 + 0
5 + 1x = -6

Add '-5' to each side of the equation.
5 + -5 + 1x = -6 + -5

Combine like terms: 5 + -5 = 0
0 + 1x = -6 + -5
1x = -6 + -5

Combine like terms: -6 + -5 = -11
1x = -11

Divide each side by '1'.
x = -11

Simplifying
x = -11

See similar equations:

| -27=-7(3b-8) | | 2h-4x=13 | | M+4m=-15 | | 2x^2+x=180 | | E=8b+12nforb | | -23=2n-7n | | 4x-2h=13 | | -18x-24=-9x+3 | | 3(5+7p)=120 | | (6x^3-4)+(2x^3+9)= | | -2(9d-8)=34+6d | | -b-4+3b=3+b | | X+17=3x-23 | | 5x+2y^3+xy^2=0 | | 8x+11-6x=5(x+7) | | 5x+2x-8=13 | | 4y-13=23# | | 48t-33=51t-69 | | -3(10)+9=-21 | | -98=2(-7+7x) | | 8(6-7y)=26 | | -3-6n=-3(1+4n)+6n | | 4x+24=8x-12 | | 1.2d-6= | | 18=28+4(-5) | | 4x+7x+8+7x+2=172 | | -5n-5(-8n+3)=13+7n | | -7-4x=2x-7(1-7x) | | 2(5-x)-5x=3-(2+4) | | 5(2)5x=15 | | -5m=4-6m | | -5v-4+7v=-25 |

Equations solver categories